Colonization of Nipa Worms (Namalycastis spp.) Based on Differences in Depth of Placement of Nipah Fronds in Kakap River of West Kalimantan - Panirman, Jennifer Vasilya; Tri Rima Setyawati; Junardi (Jurnal Biologi Tropis, 2023)
Namalycastis spp. is deposit feeder animal because it eats by utilizing organic matter and omnivorous. The existence of Namalycastis has been found inhabit naturally decomposing nipa fronds (Nypa fruticans). Data regarding the colonization of Namalycastis are currently not available. The purpose of the study is to discover the first time and the peak of colonizations and the number of individual Namalycastis based on the depth of placement of different nipa fronds in Kakap River Mangrove Area of West Borneo. Sampling was carried out at three depths: 0-10 cm, 10-20 cm, and 20-30 cm for three months within a 10 days collection period. The highest number of Namalycastis individual during the study were found in nipa fronds placed at depth of 0-10 cm is 616 individuals with the highest number found in week 4 of incubation. Soil texture in Sungai Kakap mangrove forest was dominated by dust with C-organic content decreased as the number of individual nipa worms decreased.